2012
DOI: 10.1161/hypertensionaha.112.194407
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin 1 Is Involved in Cardiac, Vascular, and Renal Fibrosis and Dysfunction

Abstract: Abstract-Cardiotrophin 1 (CT-1), a cytokine belonging to the interleukin 6 family, is increased in hypertension and in heart failure. We aimed to study the precise role of CT-1 on cardiac, vascular, and renal function; morphology; and remodeling in early stages without hypertension. CT-1 (20 g/kg per day) or vehicle was administrated to Wistar rats for 6 weeks. Cardiac and vascular functions were analyzed in vivo using M-mode echocardiography, Doppler, and echo tracking device and ex vivo using a scanning acou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 36 publications
0
54
0
3
Order By: Relevance
“…More recently, it has been reported that chronic administration of CT-1 to normotensive rats is associated with enhanced myocardial deposition of collagen type I and III fibers, increased LV volume, and reduced LV ejection fraction. 9 In addition, CT-1 knockout mice display lower arterial fibrosis than age-matched control animals. 27 Collectively, these experimental data support a cardiovascular profibrotic role for CT-1.…”
Section: Pathophysiological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been reported that chronic administration of CT-1 to normotensive rats is associated with enhanced myocardial deposition of collagen type I and III fibers, increased LV volume, and reduced LV ejection fraction. 9 In addition, CT-1 knockout mice display lower arterial fibrosis than age-matched control animals. 27 Collectively, these experimental data support a cardiovascular profibrotic role for CT-1.…”
Section: Pathophysiological Aspectsmentioning
confidence: 99%
“…In fact, in vivo studies performed in rats have shown that CT-1 induces fibrosis in different organs, including the heart. 9,10 Although CT-1 has been shown to be increased in the myocardium of patients with HF, 11,12 there are no available data on the mechanisms involved in its overproduction and its association with myocardial fibrosis in HF.…”
mentioning
confidence: 99%
“…1 Our group has described that CT-1 induces cell proliferation, hypertrophy, and secretion of extracellular matrix proteins in aortic vascular smooth muscle cells (VSMCs) in vitro 2 and in vivo, 3 suggesting a role for CT-1 in arterial fibrosis and stiffness, which both are features of aging. Furthermore, elevated plasma concentrations of CT-1 have been reported in patients with a variety of diseases, including hypertension, 4 heart failure, 5 uns table angina, 6 myocardial infarction, 7 and aortic stenosis, 8 indicating that this cytokine may contribute to the development of cardiovascular pathologies associated with aging.…”
mentioning
confidence: 99%
“…7,33,34 Vascular media thickness and ECM contents, such as collagen, fibronectin, elastin, and matrix metalloproteinase, in VSMCs were increased by CT-1 treatment in rats. 11,12 Media thickness, wall fibrosis, and inflammation were lower in CT-1-deficient mice than in wild-type controls under a normal diet. 35 These findings indicated that CT-1 plays an important role in arteriosclerosis that consists of vascular remodeling, inflammation, and calcification with aging.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9][10] CT-1 exerts cardiovascular remodeling induced by hypertensive and ischemic heart diseases and congestive heart failure, through its receptor complex glycoprotein 130 (gp130) and leukemia inhibitory factor receptor (LIFR). [11][12][13][14] Recently, CT-1 has been shown to be expressed in the intima in the early stages of atherosclerotic lesions in human carotid artery. 15 CT-1 stimulates the synthesis of inflammatory cytokines and proatherogenic molecules, such as interleukin-6, monocyte chemoattractant protein-1, and intercellular adhesion molecule-1, in human ECs.…”
mentioning
confidence: 99%